Physical Health Monitoring of Patients Prescribed Depot Antipsychotic Medication and Clozapine in the North-West Edinburgh Community Mental Health Team - Andrew Revadillo; Anna Lunan; Jack Mitchell; Kenneth Murphy; Douglas Murdie (BJPsych Open)
Aims: Antipsychotic medications are associated with metabolic syndrome and increased cardiovascular risk. Monitoring the physical health of patients receiving these medications is a key part of delivering safe and effective care.